Spectrum of Congenital Lung Malformations in Children: Experience from A Tertiary Care Center - Syed Mohsin Aijaz; Gowhar Nazir Mufti; Waseem Jan Shah; Akshat Sudhanshu; Nisar Ahmad Bhat; Aejaz Ahsan Baba; Raashid Hamid; Sheikh Khurshid Ahmed (Galenos Yayinevi, 2023)
Aim:A variety of developmental abnormalities of the tracheobronchial tree and pulmonary parenchyma are found in the newborn. There is limited data available on their presentation and clinical course from third world countries.Materials and Methods:A retrospective review of the medical records of children with congenital lung malformations was conducted at our tertiary care hospital from June, 2014 to June, 2018.Results:This study included 30 patients with 12 males and 18 females. The mean age at diagnosis was 13 months (range 1 month to 4 years). Congenital pulmonary airway malformation was the most common malformation present in 18 (60%) patients, followed by congenital lobar emphysema in 4 (13.3%), bronchogenic cyst in 3 (10%), bronchopulmonary sequestration in 2 (6.7%), bronchial atresia in 2 (6.7%) and pleuropulmonary blastoma in 1 (3.3%) patient. The most common presentation was recurrent upper respiratory tract infection (53.3%). Lobectomy was the most common surgical procedure performed in 86.6% of the patients, followed by excision of cyst in 10% of the patients. The post-operative complication rate was 30% with an overall survival rate of 93.3%. The average follow-up duration was 9 months.Conclusion:The predominant lung malformation in this study was congenital pulmonary airway malformation. Recurrent respiratory tract infection with or without respiratory distress was the most common mode of presentation. Health education to raise awareness and emphasis on antenatal ultrasonography can avoid inordinate delays in diagnosis and treatment. Surgery is curative with good long-term outcomes.